Emission Spectrum of Two-Level Single Molecule via Photon Counting Statistics (Journal of Atomic and Molecular Sciences, 2016)
In this paper, we introduce a new way to obtain the emission spectrum ofsingle molecule driven by external field. A virtual probe field is introduced to simulatethe vacuum field, which causes the spontaneous emission phenomena of the excitedsingle molecule. The statistical properties of the emission photons caused by the virtualprobe field could be used to obtain the emission spectrum of the single moleculesystem. The results demonstrate the well-known Mollow triplet splitting phenomenonas the single molecule is driven by strong external field.The abstract should provide abrief summary of the main findings of the paper.
Keywords: Two-Level System; Emission Spectrum; Generating Function.